EVALUASI PROGRAM PELAKSANAAN BIMBINGAN KARIR - Telaumbanua, Aprianus (Fakultas Ilmu Pendidikan Universitas Negeri Surabaya, 2019)
can reach their maximum self development. The purpose of this study are to describe the context, input, process and product components in guidance career program at SMK Negeri 1 Hiliserangkai Kabupaten Nias. The guidance career at vocational education mean to produces efficient and effective graduate so they have knowledge and skills to develop their selves on job industries. The study is performing by distributing questionares to the student and interview to the guidance tutor. Based on this study, we can find that the context component has been well programmed as what the student describes 84,01%. Input component has not support the implementation scheduled program which shows by student 68,61%. At process component , as student statement 65,64% shows that process component has not been effective. Product component has not been optimum shows by student statement 69,30%. Generally we can have a conclucion that the implementation career guidance program at SMK Negeri 1 Hiliserangkai has not been consistent with input and process component to achieve optimum result.